Rutin Protects Fibroblasts from UVA Radiation through Stimulation of Nrf2 Pathway - Elisabetta Tabolacci; Giuseppe Tringali; Veronica Nobile; Sara Duca; Michela Pizzoferrato; Patrizia Bottoni; Maria Elisabetta Clementi (Antioxidants, 2023)
This study explores the photoprotective effects of rutin, a bioflavonoid found in some vegetables and fruits, against UVA-induced damage in human skin fibroblasts. Our results show that rutin increases cell viability and reduces the high levels of ROS generated by photo-oxidative stress (1 and 2 h of UVA exposure). These effects are related to rutin’s ability to modulate the Nrf2 transcriptional pathway. Interestingly, activation of the Nrf2 signaling pathway results in an increase in reduced glutathione and Bcl2/Bax ratio, and the subsequent protection of mitochondrial respiratory capacity. These results demonstrate how rutin may play a potentially cytoprotective role against UVA-induced skin damage through a purely antiapoptotic mechanism.